THE MAJOR CAUSES OF CULTURAL DIFFERENCE AND CHANGE: A GLOBAL BUSINESS PERSPECTIVE WITH PHILIPPINE CONTEXT - Christopher M. Villaronte; Anik Yuesti (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2025)
Culture represents the dynamic interplay of shared traditions, socio-economic structures, and adaptive transformations shaped by historical and global forces. This study examines the primary causes of cultural difference and change, focusing on the Philippine socio-cultural landscape within the broader context of global business environments. Anchored in theoretical frameworks and empirical evidence, the research identifies colonization, regional diversity, labor migration, digital technologies, and globalization as key drivers of cultural evolution. Through a qualitative content analysis of secondary sources and Philippine case studies, findings reveal that cultural transformation in the Philippines is characterized by a tension between cultural preservation and global adaptation. The study highlights cultural hybridity, the impact of diaspora communities, indigenous resistance, and digital disruptions as pivotal dimensions of this evolving identity, and explores how these transformations inform global business strategies such as localization, workforce development, CSR, and market entry.